The industrial internet of things (IIoT): An analysis framework - Boyes, Hugh; Hallaq, Bil; Cunningham, Joe; Watson, Tim (Computers in industry, 2018)
•Existing definitions of the Internet of Things (IoT) and allied terms are reviewed.•A robust definition of Industrial Internet of Things (IIoT) is proposed.•An analysis framework for characterisation and classification of IIoT devices is provided.•Gaps in the current literature and understanding of IIoT are identified. Historically, Industrial Automation and Control Systems (IACS) were largely isolated from conventional digital networks such as enterprise ICT environments. Where connectivity was required, a zoned architecture was adopted, with firewalls and/or demilitarized zones used to protect the core control system components. The adoption and deployment of ‘Internet of Things’ (IoT) technologies is leading to architectural changes to IACS, including greater connectivity to industrial systems. This paper reviews what is meant by Industrial IoT (IIoT) and relationships to concepts such as cyber-physical systems and Industry 4.0. The paper develops a definition of IIoT and analyses related partial IoT taxonomies. It develops an analysis framework for IIoT that can be used to enumerate and characterise IIoT devices when studying system architectures and analysing security threats and vulnerabilities. The paper concludes by identifying some gaps in the literature.